2011
DOI: 10.1021/la201073m
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Dispersion and Aggregation in Polymer Nanocomposites: Insights from Molecular Dynamics Simulation

Abstract: It is a great challenge to fully understand the microscopic dispersion and aggregation of nanoparticles (NPs) in polymer nanocomposites (PNCs) through experimental techniques. Here, coarse-grained molecular dynamics is adopted to study the dispersion and aggregation mechanisms of spherical NPs in polymer melts. By tuning the polymer-filler interaction in a wide range at both low and high filler loadings, we qualitatively sketch the phase behavior of the PNCs and structural spatial organization of the fillers m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
245
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 304 publications
(273 citation statements)
references
References 38 publications
(63 reference statements)
18
245
3
2
Order By: Relevance
“…[16][17][18][19][20][21][22][23][24][25][26] Concerning the nanofiller size and shape, computational studies have focused on fillers whose size is comparable to the characteristic length scales of the polymer matrix, namely the radius of gyration of the polymers or the size of their monomers. 21 mal NP dispersion and strong polymer-NP interactions 27 have shown that the smaller NPs have better reinforcing properties, leading to tougher PNCs. 17,19,28 Furthermore, the increase in the aspect ratio of the nanoparticles, that finds an experimental correspondence in carbon nanotubes 10,29 or clay sheets, 10 has been observed to lead to an increase of the mechanical reinforcement of PNC.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26] Concerning the nanofiller size and shape, computational studies have focused on fillers whose size is comparable to the characteristic length scales of the polymer matrix, namely the radius of gyration of the polymers or the size of their monomers. 21 mal NP dispersion and strong polymer-NP interactions 27 have shown that the smaller NPs have better reinforcing properties, leading to tougher PNCs. 17,19,28 Furthermore, the increase in the aspect ratio of the nanoparticles, that finds an experimental correspondence in carbon nanotubes 10,29 or clay sheets, 10 has been observed to lead to an increase of the mechanical reinforcement of PNC.…”
Section: Introductionmentioning
confidence: 99%
“…We model the PNC in a regime of strong polymer-filler interactions and optimal degree of dispersion [18]. Fillers are small if compared to the radius of gyration of the chains.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is reasonable to apply the theory of molecular dynamics to the nanoparticle system and thus the thermal motion of nanoparticles is equivalent to the thermal motion of macromolecules, which is accepted in many literatures [49][50][51][52]. In the following, we will adopt the vibration movement of the nanoparticle, denoted in Figure 1b, representing the complicated thermal motion to show the effect of the thermal-electric cross coupling on heat transport in nanofluids.…”
Section: Model Of Nanofluidsmentioning
confidence: 99%